Comparison of BTSE-RGD with DOTA-RGD as a potential imaging agent for tumors1. Issue 67 (24th July 2015) - Varshney, Raunak; Singh, Sweta; Tiwari, Anjani K.; Mathur, Rashi; Singh, Shivani; Panwar, Puja; Yadav, Neelam; Chutani, Krishna; Singh, B.; Mishra, Anil K.
<x xml:space="preserve">Abstract</x> RGD and its analogues are very important compounds and can be used as potential tumor-targeting agents.